81PComprehensive genomic and transcriptomic profiling in advanced-stage cancers and rare malignancies: Clinical results from the MASTER trial of the German Cancer Consortium. (7th November 2019) - Horak, P; Kreutzfeldt, S; Mock, A; Heining, C; Heilig, C E; Möhrmann, L; Uhrig, S; Hübschmann, D; Beck, K; Richter, D; Schlenk, R F; Klink, B; et al.
Abstract: Background: Precision oncology, guided by high-resolution molecular diagnostics, refers to the ability to identify patients that are likely to respond to specific anticancer therapies. Although recent studies demonstrated the utility of comprehensive molecular profiling based on whole-exome/genome sequencing and transcriptome sequencing to guide therapeutic decisions in individual patients, many questions remain unanswered. Methods: We report the clinical results of MASTER, a multicenter, cross-entity registry trial for prospective, biology-driven stratification of younger adults with advanced-stage cancer and patients with rare tumors conducted by NCT Heidelberg/Dresden and the German Cancer Consortium. From 2013 to 2018, we discussed the molecular profiles from 1, 311 poor-prognosis patients in a cross-institutional molecular tumor board. Results: Evaluation of the data based on a standardized bioinformatics workflow and manual curation by a team of translational oncologists allowed categorization into 7 intervention baskets and formulation of evidence-based recommendations for clinical management in more than 80% of patients, which could be acted upon in approximately one third of cases. Overall response and disease control rates on molecularly guided treatment were improved compared to prior systemic therapies, which translated into a progression-free survival ratio of greater than 1.3 in more than 30% of cases. Comprehensive genomic profiling also provided relevant diagnostic information that led to categorization of some tumors based on genotype and subsequent histopathologic reevaluation. Conclusions: Our experience demonstrates that comprehensive molecular profiling in a multi-institutional clinical setting is feasible, complements and advances routine molecular diagnostics, and creates clinically meaningful therapeutic opportunities. Current and future initiatives of the MASTER network are focused on the standardization of variant classification and evidence levels in molecular tumor boards; the implementation of molecularly stratified basket trials; and the integration of additional layers of patient characterization. Legal entity responsible for the study: The authors. Funding: German Cancer Consortium, Heidelberg Institute for Personalized Oncology. Disclosure: W. Weichert: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): MSD; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): BMS; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony: Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Takeda; Research grant / Funding (self): Bruker. All other authors have declared no conflicts of interest.